2018
DOI: 10.3855/jidc.9789
|View full text |Cite
|
Sign up to set email alerts
|

Dissemination of ST101 blaOXA-48 producing Klebsiella pneumoniae at tertiary care setting

Abstract: Introduction: The worldwide dissemination of the acquired carbapenemases in Gram-negative bacteria is a strongly expressed demand for the emergence of post antibiotic era. The aim of this study was to test the production of carbapenemase by Klebsiella pneumoniae strains isolated from hospitalized cancer patients and to investigate the genetic relationship of carbapenemase producing carbapenem resistant K. pneumoniae using multilocus sequence typing (MLST). Methodology: Antibiotic susceptibility testing a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Colistin-resistant K. pneumoniae isolates in our collection belong to various clones, as assessed by multilocus sequence typing, suggesting considerable genetic diversity present in the same hospital. Of these, ST101 is a major drug-resistant strain, not only in Egypt, but also worldwide [33, 34]. Strikingly, we seem to have found the first mcr-1 positive ST11 strain in Egypt.…”
Section: Discussionmentioning
confidence: 78%
“…Colistin-resistant K. pneumoniae isolates in our collection belong to various clones, as assessed by multilocus sequence typing, suggesting considerable genetic diversity present in the same hospital. Of these, ST101 is a major drug-resistant strain, not only in Egypt, but also worldwide [33, 34]. Strikingly, we seem to have found the first mcr-1 positive ST11 strain in Egypt.…”
Section: Discussionmentioning
confidence: 78%
“…28 CRE Figure 8 Summary of the prevalence (%) of carbapenemase and ESBL genes in K. pneumoniae. Notes: Data from references 40,[55][56][57][58][59][60][61][62]70,80,[94][95][96][97][98][99] . a % of carbapenemase-resistant/-producing K. pneumoniae; b % of MDR K. pneumoniae; c % of ESBL-producing/third-generation cephalosporin-resistant K. pneumoniae; d % of ertapenem non-susceptible K. pneumoniae.…”
Section: Discussionmentioning
confidence: 99%
“…Among the various members of CRE, CRKP have received the most attention because they have the greatest potential to contribute to the overall problem of AR [ 37 , 38 ]. In a study conducted in Egypt, ElMahallawy et al [ 39 ] reported the detection of OXA-48-like positive CRE in clinical isolates, which emphasized the prevalence of CRE in sub-Sahara Africa and this calls for more studies to be carried out in the region. In South Africa, reports on the presence of ARGs (specifically carbapenemase-producing genes) in isolates from different environmental niches are scarce, however, various studies on the high occurrence of ESBL have been previously reported [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%